MOTIVASI BELAJAR DALAM FILM ANIMASI NARUTO UZUMAKI (Studi Perspektif Psikologi Belajar) - Rofi’ah, Siti; Sari, Siti Destia Retno (Al Tadib : Jurnal Ilmu Pendidikan, 2015)
This article is aimed at describing the motivationinspired by Japanese animation Uzumaki Naruto, the hero ofJapanese animation series that became a favorite both from thechildren to adults. Naruto is a figure described as a child whocame from the village of Konoha, the Fire Nation who livedalone and did not know her father was then known that thefather is the 4th Hokage Minato and his mother UshinaUzumaki is the owner Kyūbi. Naruto grows into a man whohad a vision for the future that is becoming Hokage so thatpeople recognize its existence when it was shunned becausekyubi society that is in itself cause damage to the village ofKonoha. The vision makes Naruto gets better learning.Therefore, the result is,: 1. Motivation is the impetus, the will,or will power to awaken and direct the behavior of individuals,intrinsic and extrinsic motivation. 2. Learning is a relativelypermanent change in behavior as a result of their experienceand training 3. Naruto movie that is associated with learningmotivation of extrinsic motivation, self-esteem and also themotive actualization. Naruto is also associated with learning,because in it, there is a correlation between the activity oflearning, elements of learning, and learning characteristics, aswell.Keyword: Motivation, Naruto Uzumaki, Psychology